1984
DOI: 10.1002/gepi.1370010202
|View full text |Cite
|
Sign up to set email alerts
|

Genetic covariation between neuroticism and the symptoms of anxiety and depression

Abstract: A genetic analysis of the trait of neuroticism and symptoms of anxiety and depression in 3,810 pairs of adult MZ and DZ twins is reported. Differences between people in these measures can be explained simply by differences in their genes and in their individual environmental experiences. There is no evidence that environmental experiences that are shared by cotwins, such as common family environment or social influences, are important. There are differences between the sexes in gene action affecting neuroticis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
281
2
4

Year Published

1986
1986
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(313 citation statements)
references
References 31 publications
26
281
2
4
Order By: Relevance
“…One such trait is neuroticism. 81,82 Large populationbased twin studies have found a substantial genetic correlation between neuroticism and depression [83][84][85] and consequently it has been used as a marker for depression vulnerability. [86][87][88][89][90][91] Sen et al 92 investigated a putative association between depression vulnerability and a single-nucleotide polymorphism in the 5 0 pro-domain of BDNF, which results in an aminoacid substitution of valine (Val) to methionine (Met) at codon 66 (Val66Met).…”
Section: Evidence Formentioning
confidence: 99%
“…One such trait is neuroticism. 81,82 Large populationbased twin studies have found a substantial genetic correlation between neuroticism and depression [83][84][85] and consequently it has been used as a marker for depression vulnerability. [86][87][88][89][90][91] Sen et al 92 investigated a putative association between depression vulnerability and a single-nucleotide polymorphism in the 5 0 pro-domain of BDNF, which results in an aminoacid substitution of valine (Val) to methionine (Met) at codon 66 (Val66Met).…”
Section: Evidence Formentioning
confidence: 99%
“…There was no evidence for association in the Netherlands family sample (N = 1148, wave 6, analyzed using quantitative transmission-disequilibrium test (QTDT), P = 0.88). The Australian family sample was analyzed using the age and sex transformed scores 42 based on the full 23-item EPQ-R N scale and the 10-item Kessler Psychological Distress scale 43 (K10), a measure of current non-specific psychological distress in the anxiety-depression spectrum. Individuals were considered 'affected' for EPQ-R and K10 if their residual scores were in the top 5, 10, 15 and 20 percentile of available residuals.…”
Section: Replicationmentioning
confidence: 99%
“…Under this view, more extreme levels of a particular temperamental trait would be a necessary although not sufficient element of a corresponding psychiatric disorder. A large twin study conducted in Australia (Jardine, Martin, & Henderson, 1984) reported the genetic correlation between neuroticism and anxiety to be approximately .8. Hettema, Prescott, and Kendler (2004) recently found evidence that not only is there a high degree of correlation between neuroticism and generalized anxiety disorder (GAD) but that the two conditions may involve some of the same genes.…”
Section: Introductionmentioning
confidence: 99%